Crossed leg sign is associated with severity of unilateral spatial neglect after stroke - Luvizutto, Gustavo José; Neto, Eduardo de Moura; Resende, Luiz Antônio de Lima [UNESP]; Nunes, Hélio Rubens de Carvalho [UNESP]; Betting, Luiz Eduardo Gomes Garcia [UNESP]; Bazan, Rodrigo [UNESP] (Frontiers, 2018)
Background: The crossed leg sign in patients with right hemisphere stroke is thought to be associated with perceptual disorders, such as unilateral spatial neglect (USN). The aim of this study was to compare the crossed leg sign with the severity of USN during the acute phase of stroke. Experimental procedures: This was an observational and prospective clinical study of individuals with a diagnosis of right parietal stroke, as confirmed by neuroimaging. The occurrence of the crossed leg sign, the time at which this occurred after the stroke, and a clinical diagnosis of USN were measured and recorded. The patients' age, sex, and lesion severity, as determined by the National Institutes of Health Stroke Scale and Glasgow coma scale, were included in the analyses as confounding variables. The outcome of interest was the degree of USN, as measured by the cancellation and bisection tests. Binary logistic regression was used to analyze the effect of crossed leg syndrome on the severity of USN. In the adjusted multiple regression model, a p-value of < 0.05 was considered statistically significant. Results: Overall, 60 patients were included in this study. There were no associations between patient demographics and the presence of the crossed leg sign. There was, however, an association between the crossed leg sign and the absolute value of the deviation in the line bisection test (B = -0.234; p = 0.039). The crossed leg sign was not associated with other measures of USN. Conclusion: Based on the results of our study, we can conclude that a crossed leg sign in the acute phase of stroke is associated with USN severity, specifically the misinterpretation of the midline.
Keywords: Cerebrovascular disease; Crossed leg sign; Hemispatial neglect; Stroke; Unilateral spatial neglect